2016
DOI: 10.1371/journal.pone.0149506
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Vertical Stratification and Guild Composition of Saproxylic Beetles in Lowland and Montane Forests: Similar Patterns despite Low Faunal Overlap

Abstract: ObjectiveThe finer scale patterns of arthropod vertical stratification in forests are rarely studied and poorly understood. Further, there are no studies investigating whether and how altitude affects arthropod vertical stratification in temperate forests. We therefore investigated the fine-scale vertical stratification of diversity and guild structure of saproxylic beetles in temperate lowland and montane forests and compared the resulting patterns between the two habitats.MethodsThe beetles were sampled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 48 publications
(65 reference statements)
2
24
0
Order By: Relevance
“…Substantially lesser attention has been paid to the investigation of relict saproxylic beetles bound to montane and boreal forests (but see Siitonen & Saaristo, 2000;Wikars, 2004; Bla zyte-Cere skien_ e & Karalius, 2012; Ranius et al, 2014;Ka s ak & Foit, 2018;Kostanjsek et al, 2018), though even these forests have not been spared from commercial management (Odor et al, 2006), negatively affecting their original biota. Moreover, montane forests are unique ecosystems that differ in many aspects from lowland forests, and thus, they harbour specific saproxylic beetle fauna, including relict species (Sl ama, 1998;Weiss et al, 2016). Additionally, in many regions the largest forest complexes have been preserved on mountains, which may serve as refugia for regional saproxylic beetle diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Substantially lesser attention has been paid to the investigation of relict saproxylic beetles bound to montane and boreal forests (but see Siitonen & Saaristo, 2000;Wikars, 2004; Bla zyte-Cere skien_ e & Karalius, 2012; Ranius et al, 2014;Ka s ak & Foit, 2018;Kostanjsek et al, 2018), though even these forests have not been spared from commercial management (Odor et al, 2006), negatively affecting their original biota. Moreover, montane forests are unique ecosystems that differ in many aspects from lowland forests, and thus, they harbour specific saproxylic beetle fauna, including relict species (Sl ama, 1998;Weiss et al, 2016). Additionally, in many regions the largest forest complexes have been preserved on mountains, which may serve as refugia for regional saproxylic beetle diversity.…”
Section: Introductionmentioning
confidence: 99%
“…This is contrasts with previous studies that illustrated higher richness of saproxylic species at lower positions (Hammond et al 2004;Vodka et al 2009;Weiss et al 2016). Although sun-exposure has been reported as an important factor for saproxylic beetle distribution (Brunet and Isacsson 2009), this variable was not relevant in our study because we sampled the logs under the dense canopy of plantation forests.…”
Section: Discussionmentioning
confidence: 58%
“…Several studies have revealed differences between the saproxylic beetle assemblages in canopy and understory strata (Wermelinger et al 2007;Vodka et al 2009;Gossner et al 2013a) and between snags and fallen logs (Väisänen et al 1993;Hammond et al 2004;Ulyshen and;Hanula 2009). However, there are few studies on vertical distribution of saproxylic species within the space between the canopy and forest floor strata (Foit 2010;Weiss et al 2016) and information on species assemblages within snag trunks remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that abundance, species composition, diversity and/or body size distribution vary vertically in the following insect groups or guilds: saproxylic beetles collected by flight intercept traps set from 0.4 to 21 m (Weiss et al . ) and by both flight intercept and yellow pan traps set from 0 to 20 m (Wermelinger et al . ); Coleoptera and Diptera communities sampled by non‐attracting flight intercept traps and trunk traps set from 1.5 to 20 m (Maguire et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Weiss et al . ; Ulyshen & Sheehan ), yellow pan traps (Wermelinger et al . ) and UV light traps (Sutton et al .…”
Section: Introductionmentioning
confidence: 99%